Characterisation of tissue factor‐bearing extracellular vesicles with AFM: comparison of air‐tapping‐mode AFM and liquid Peak Force AFM. Issue 1 (27th August 2013) - Hardij, Julie; Cecchet, Francesca; Berquand, Alexandre; Gheldof, Damien; Chatelain, Christian; Mullier, François; Chatelain, Bernard; Dogné, Jean‐Michel
Abstract : Introduction: Extracellular vesicles (EVs) are shed from cells and carry markers of the parent cells. Vesicles derived from cancer cells reach the bloodstream and locally influence important physiological processes. It has been previously shown that procoagulant vesicles are circulating in patients' fluids. These EVs are therefore considered as promising biomarkers for the thrombotic risk. Because of their small size, classical methods such as flow cytometry suffer from limitation for their characterisation. Atomic force microscopy (AFM) has been proposed as a promising complementary method for the characterisation of EVs. Objectives: The objectives of this study are: (a) to develop and validate AFM with specific antibodies (anti‐TF) and (b) to compare air and liquid modes for EVs' size and number determination as potential biomarkers of the prothrombotic risk. Methods: AFM multimode nanoscope III was used for air tapping mode (TM). AFM catalyst was used for liquid Peak Force Tapping (PFT) mode. Vesicles are generated according to Davila et al.'s protocol. Substrates are coated with various concentrations of antibodies, thanks to ethanolamine and glutaraldehyde. Results: Vesicles were immobilised on antibody‐coated surfaces to select tissue factor (TF)‐positive vesicles. The size range of vesicles observed in liquid PFT mode is 6–10 times higher than in air mode. This corresponds to the data found in the literature. Conclusion: We recommend liquid PFT mode to analyse vesicles on 5 µg/ml antibody‐coated substrates.